Outcome and right ventricle remodelling after valve replacement for pulmonic stenosis. Issue 16 (23rd November 2021) - Laflamme, Emilie; Wald, Rachel M; Roche, S Lucy; Silversides, Candice K; Thorne, Sara A; Colman, Jack M; Benson, Lee; Osten, Mark; Horlick, Eric; Oechslin, Erwin; Alonso-Gonzalez, Rafael
Abstract : Background: Complications and need for reinterventions are frequent in patients with pulmonary valve stenosis (PVS). Pulmonary regurgitation is common, but no data are available on outcome after pulmonary valve replacement (PVR). Methods: We performed a retrospective analysis of 215 patients with PVS who underwent surgical valvotomy or balloon valvuloplasty. Incidence and predictors of reinterventions and complications were identified. Right ventricle (RV) remodelling after PVR was also assessed. Results: After a median follow-up of 38.6 (30.9–49.4) years, 93% of the patients were asymptomatic. Thirty-nine patients (18%) had at least one PVR. Associated right ventricular outflow tract (RVOT) intervention and the presence of an associated defect were independent predictors of reintervention (OR: 4.1 (95% CI 1.5 to 10.8) and OR: 3.6 (95% CI 1.9 to 6.9), respectively). Cardiovascular death occurred in 2 patients, and 29 patients (14%) had supraventricular arrhythmia. Older age at the time of first intervention and the presence of an associated defect were independent predictors of complications (OR: 1.0 (95% CI 1.0 to 1.1) and OR: 2.1 (95% CI 1.1 to 4.2), respectively). In 16 patients, cardiac magnetic resonance before and after PVR was available. The optimal cut-off values for RV volume normalisation were 193 mL/m 2 for RV end-diastolic volume indexed(sensitivity 80%, specificity 64%) and 100 mL/m 2 for RV end-systolic volume indexed(sensitivity 80%, specificity 56%). Conclusions: Previous RVOT intervention, presence of an associated defect and older age at the time of first repair were predictors of outcome. More data are needed to guide timing of PVR, and extrapolation of tetralogy of Fallot guidelines to this population is unlikely to be appropriate.